2003
DOI: 10.1021/jf030158d
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Chlorophylls and Carotenoids in Major Teas by High-Performance Liquid Chromatography with Photodiode Array Detection

Abstract: The separation and identification of pigments, chlorophylls, and carotenoids of seven teas and fresh leaf of tea (Camellia sinensis) by high-performance liquid chromatography (HPLC) are described. HPLC was carried out using a Symmetry C(8) column with a photodiode array detector. Pigments were eluted with a binary gradient of aqueous pyridine solution at a flow rate of 1.0 mL/min at 25 degrees C. HPLC analyses achieved the separation of more than 100 pigment peaks, and 79 pigment species, 41 chlorophylls, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 16 publications
1
44
1
Order By: Relevance
“…Nevertheless, the exact contribution of carotenoids to the quality of taste and colour of green tea has not previously reported yet. This data showed that carotenoids concentrations did not correlate with any quality scores (Table 5), possibly because of low solubility in hot water (Suzuki & Shioi, 2003). Neither of these CIELAB parameters correlated significantly with sensory scores, showing limited applicability of these parameters for the assessment of quality of Longjing teas and not agreeing with the conclusion reached in experiments working with other types of teas (Liang et al ., 2003, 2005).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, the exact contribution of carotenoids to the quality of taste and colour of green tea has not previously reported yet. This data showed that carotenoids concentrations did not correlate with any quality scores (Table 5), possibly because of low solubility in hot water (Suzuki & Shioi, 2003). Neither of these CIELAB parameters correlated significantly with sensory scores, showing limited applicability of these parameters for the assessment of quality of Longjing teas and not agreeing with the conclusion reached in experiments working with other types of teas (Liang et al ., 2003, 2005).…”
Section: Resultsmentioning
confidence: 93%
“…During processing, carotenoids degrade to form a number of volatile compounds, highlighting their contribution to aromatic quality of tea (Ravichandran, 2002). Some violaxanthin is also conversed to auroxanthin leading to decreases of the number of carotenoids species (Suzuki & Shioi, 2003). Nevertheless, the exact contribution of carotenoids to the quality of taste and colour of green tea has not previously reported yet.…”
Section: Resultsmentioning
confidence: 99%
“…The spectrum detected in wild-type untreated plants (peak 3, Supplemental Fig. 5F) showed no phytoene peaks but the characteristics of the compound lutein (Suzuki and Shioi, 2003), which is derived from subsequent series of desaturations and cyclizations in the carotenoid biosynthesis pathway when PDS is active. PDS-RNAi transgenic lines, which showed an albino phenotype, also contained two peaks with virtually identical spectra to the spectrum of phytoene from norflurazon-treated wild-type tissue (Supplemental Fig.…”
Section: Phytoene Accumulates In Bleached Tissue As a Results Of Rnai-mentioning
confidence: 99%
“…Using standards, relative retention times and spectral characteristics (Edelenbos et al, 2001;Kimura and Rodriguez-Amaya, 2003;Suzuki and Shioi, 2003), various chloroplast pigments were identified (Fig. 1).…”
Section: Article In Pressmentioning
confidence: 99%